Selective Transformation of CO2 and H2 into Lower Olefins over In2O3‐ZnZrOx/SAPO‐34 Bifunctional Catalysts. Issue 15 (9th July 2019) - Dang, Shanshan; Li, Shenggang; Yang, Chengguang; Chen, Xinqing; Li, Xiaopeng; Zhong, Liangshu; Gao, Peng; Sun, Yuhan
Abstract: Because lower olefins (C2 = –C4 = ) are important bulk petrochemicals, their direct production from CO2 hydrogenation is highly attractive. However, the selectivity towards C2 = –C4 = by the modified Fischer–Tropsch synthesis is restricted to 56.7 % with high undesired methane selectivity. Here, a series of bifunctional catalysts containing In2 O3 ‐ZnZrO x oxides and various SAPO‐34 zeolites with different crystal sizes (0.4–1.5 μm) and pore structures was developed for the production of lower olefins by CO2 hydrogenation. The C2 = –C4 = selectivity reached as high as 85 % among all hydrocarbons with very low CH4 selectivity of only 1 % at a CO2 conversion of 17 %. This demonstrated that the small crystal size, hierarchical pore structure, and appropriate amount of Brønsted acid sites of SAPO‐34 endowed the bifunctional catalysts with high C2 = –C4 = selectivity. This work shows an efficient way for developing bifunctional catalysts for direct CO2 hydrogenation to lower olefins. Abstract : Get lower olefins : A series of bifunctional catalysts containing In2 O3 ‐ZnZrO x and various SAPO‐34 zeolites with different sizes and pore structures is presented for CO2 hydrogenation to lower olefins. The C2 = –C4 = selectivity reaches as high as 85 % among all hydrocarbons with very low CH4 selectivity of only 1 % at a CO2 conversion of 17 %.